2015
DOI: 10.1186/s12876-015-0304-4
|View full text |Cite
|
Sign up to set email alerts
|

Relation of cholesterol metabolism to pediatric gallstone disease: a retrospective controlled study

Abstract: BackgroundCholesterol metabolism may be involved in pediatric gallstone disease. We aimed to reveal cholesterol metabolites and phytosterols and their relation to stone composition of sterols in children having black pigment and cholesterol stones.MethodsWe performed retrospective controlled clinical study, in which we examined parameters of cholesterol metabolism and liver function values in serum (n = 28) and gallstones (n = 46) of consecutively cholecystectomized children. Serum values of age-, body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
2
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
(27 reference statements)
1
18
2
1
Order By: Relevance
“…In this population-based case-control study, high serum LDL levels and low levels of HDL were significantly associated with an increased risk of biliary calculus. This finding supports the role of serum lipids in gallstones and biliary carcinogenesis, which is consistent with previous cross-sectional and prospective studies of serum lipid and gallstones showing that high TG and low cholesterol levels are associated with gallstone risk [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…In this population-based case-control study, high serum LDL levels and low levels of HDL were significantly associated with an increased risk of biliary calculus. This finding supports the role of serum lipids in gallstones and biliary carcinogenesis, which is consistent with previous cross-sectional and prospective studies of serum lipid and gallstones showing that high TG and low cholesterol levels are associated with gallstone risk [17][18][19][20][21].…”
Section: Discussionsupporting
confidence: 92%
“…Children with increased risk for the disease are prematures that have been administered with furosemid and those that were administered parenteral therapy [1]. Predisposing factors for gallbladder stones are: children with total parenteral nutrition, ileum resection, sepsis and haemolitic diseases [1] [9] [23] [24]. In infants, cholelithiasis can spontaneously regress (fetal cholelithiasis) but they can too manifest themselves with clinical symptoms and complications due to predisposing factors [6] [20].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two studies were identified, of which five studies were performed in patients with steatosis [95][96][97][98][99], eleven studies in patients with cholestasis [100][101][102][103][104][105][106][107][108][109][110], and six studies included patients with liver diseases related to cirrhosis or necrosis [111][112][113][114][115][116] (Table 8). [102] Cases (n = 45) 3.00 ± 1.10 ↑ Controls (n = 80)…”
Section: Serum Non-cholesterol Sterol Markers In Subjects With Liver mentioning
confidence: 99%